Genomic Prediction for Whole Weight, Body Shape, Meat Yield, and Color Traits in the Portuguese Oyster Crassostrea angulata - Vu, Sang V.; Knibb, Wayne; Gondro, Cedric; Subramanian, Sankar; Nguyen, Ngoc T. H.; Alam, Mobashwer; Dove, Michael; Gilmour, Arthur R.; Vu, In Van; Bhyan, Salma; Tearle, Rick; Khuong, Le Duy; et al. (Frontiers in Genetics, 2021)
Genetic improvement for quality traits, especially colour and meat yield has been limited in aquaculture because assessment of these traits requires the animals be slaughtered first. Genotyping technologies do however provide an opportunity to improve selection efficiency for these traits. The main purpose of this study is to assess the potential for using genomic information to improve meat yield (soft tissue weight, condition index), body shape (cup and fan ratios), colour (shell and mantle), and whole weight traits at harvest in the Portuguese oyster, Crassostrea angulata. The study consisted of 647 oysters: 188 oysters from 57 full-sib families from the first generation and 459 oysters from 33 full-sib families from the second generation. The number per family ranged from 2 to 8 for the first and 12 to 15 oysters for the second generation. After quality control, a set of 13,048 markers were analysed to estimate genetic parameters (heritability and genetic correlation) and predictive accuracy of genomic selection for these traits. The multi-locus mixed model analysis indicated high estimates of heritability for meat yield traits: 0.43 for soft tissue weight and 0.77 for condition index. Estimated genomic heritabilities were 0.45 for whole weight, 0.24 for cup ratio, 0.33 for fan ratio and ranged from 0.14 to 0.54 for colour traits. Genetic correlations among whole weight, meat yield and body shape traits were favourably positive suggesting that selection for whole weight would have beneficial effects on meat yield and body shape traits. Of paramount importance, the genomic prediction showed moderate to high accuracy for the traits studied (0.38-0.92). Therefore, there are good prospects to improve whole weight, meat yield, body shape and colour traits using genomic information. A multi-trait selection program using the genomic information can boost the genetic gain and minimise inbreeding in the long term for this population.